Treatment outcomes of ischemic stroke with and without administration of thrombolytic therapy: a comparative study - Varahabhatla Vamsi; Vinisha Tekwani; Vedula Ushakiranmayi; Sikorska, Marina; Сікорська, Марина Володимирівна (My University, 2018)
Introduction: Intravenous thrombolytic therapy at the cerebral circulation within the first 3 hours of ischemic stroke onset offers substantial net benefits for virtually all patients with potentially disabling deficits. Aim: Evaluate the course of the disease in patients with ischemic stroke with a clinical improvement of the neurological deficit during the 3-hour window period in the groups of patients who received and did not receive intravenous thrombolysis. Methods: A descriptive, retrospective study was performed, in which we reviewed demographical, clinical, tomographical, procedural records of the patients at 6th Municipal Clinical Hospital, Zaporozhye from 2010-2017. A total of 78 case histories were analyzed, 12 were patients with Intravenous thrombolytic therapy and 66 with traditional therapy. The results of the treatment were assessed on the basis of NIHSS scale and the Modified Rankin scale after 90 days after treatment. The statistical data was processed using STATISTICA® 7.0. Results: In the group of patients with Intravenous thrombolytic therapy, none of the patients showed clinical worsening. In the 2nd group, 21 patients showed an increase in neurologic deficit in the first 3-5 days after hospitalization. The NIHSS score in the 1stgroup, when deciding on Intravenous thrombolytic therapy and at discharge for 20 days, was 6 ±3,8 and 0,5 ±0,2, respectively. In the 2nd group; 6 ±2,9 and 4 ±1,11. According to the modified Rankine scale, after 3 months in the first group, the index was 0,5 ±0,1 (≤ 1 in 8 patients); in the second group 1 ±0,3. Conclusions: Intravenous thrombolysis in patients with spontaneous early regression of neurological
Keywords: stroke; thrombolytic therapy; depression; quality of life